A qualidade dos serviços da Atenção Primária à Saúde na perspectiva de usuários, gestores e profissionais de saúde - Borges, Luana Viviani (Universidade Federal de São Carlos, 2023)
This study sought to understand the perception of users, workers and municipal managers in relation to access and quality of Primary Health Care (PHC) services. An exploratory field research was carried out, with a qualitative approach, in which an individual semi-structured script was used for each population interviewed remotely, being transcribed and analyzed according to content analysis and analyzing flowchart. It was possible to identify changes in the PHC flow and its relationship with the Health Care Network (RAS); the potential and difficulties involving access and quality of services at the gateway to the SAN before and during the covid-19 pandemic. These changes affected essential attributes of PHC, such as longitudinality, coordination of care, bonding with the user and health resoluteness, revealing a disjointed RAS, reflections of the process of dismantling the Unified Health System.
Quality of Primary Health Care services from the perspective of users, managers and health professionals
La calidad de los servicios de Atención Primaria de Salud en la perspectiva de los usuarios, gestores y profesionales de la salud
Keywords: Atenção Primária à Saúde; Acesso aos serviços de saúde; Qualidade da assistência à saúde; COVID-19; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM DE SAUDE PUBLICA